Kepribadian dan Kewirausahaan: Studi Big Five Personality pada Mahasiswa Mata Kuliah Pengembangan Kepribadian Entrepreneurial - Hani Sirine; Hasri Nur Wicaksono (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze how each dimension of the Big Five personality traits (extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience) influences entrepreneurial interest among students. The research employs a quantitative approach, with data collected from students at Universitas Kristen Satya Wacana enrolled in the Entrepreneurial Personality Development course. A total of 36 respondents participated in the study. The results indicate that the Big Five personality traits influence students' entrepreneurial interest, except for neuroticism, which tends to avoid uncertainty. Students with high extraversion, conscientiousness, and openness can be further developed through training, while those with high agreeableness need to enhance their negotiation skills and decisiveness. Meanwhile, students with high neuroticism require support in stress management and risk-taking confidence.